Lust, Oblivion and the Archive Fever: Vision as Hypomnesis of "The Dead" - Jukić, Tatjana (2008)
Structurally, "The Dead" labors as a kind of archive to Joyce's Dubliners. This archive is organized not only around the very position of finality ("the Dead" as the last story in the collection), where the narrative cannot but be summing up the collection's various concerns and organizing them as its memory— where, specifically from within this memory, Dubliners coheres into a collection to begin with, and starts laboring as one. As effectively perhaps this archive labors where "The Dead" exposes the very structures of memory, finality and collectivism as symptoms of what in archiving survives as hypomnesis, or else of what in archiving labors as an agent provocateur of mnemotechnology. My presentation aims to address this specific agency or survival in "The Dead" as a position where to think further Joyce as an agent provocateur of psychoanalysis and of philosophy themselves (most notably in the work of Jacques Derrida and Gilles Deleuze).